1991
DOI: 10.1002/j.1551-8833.1991.tb07253.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soils on the Permeation of Plastic Pipes by Organic Chemicals

Abstract: Polybutylene pipes (0.75 in.) buried in both water‐saturated and unsaturated soils contaminated with toluene, trichloroethylene, 1,2‐dichlorobenzene, and o‐chlorophenol were permeated to detectable levels in 1 to 150 days, depending on the organic chemical and its concentration. Comparison of these results with pipe‐bottle experiments containing no soil showed that the concentration of organic chemical in the soil pore controls the rate of organic chemical permeation through buried plastic pipes. The results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Four levels of gasoline-contaminated soil were prepared by spiking 1 kg of the sand-topsoil mixture with known amounts of premium gasoline and mixing the soil by rotating the soil container for one week. The volumetric moisture content of the soil was adjusted to approximately 10%, which was above the water content of soils equilibrated at a relative humidity > 98% (Holsen et al, 1991b). The amounts of BTEX sorbed onto the four soils were determined using methanol extraction and analyzed by gas chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four levels of gasoline-contaminated soil were prepared by spiking 1 kg of the sand-topsoil mixture with known amounts of premium gasoline and mixing the soil by rotating the soil container for one week. The volumetric moisture content of the soil was adjusted to approximately 10%, which was above the water content of soils equilibrated at a relative humidity > 98% (Holsen et al, 1991b). The amounts of BTEX sorbed onto the four soils were determined using methanol extraction and analyzed by gas chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The case of benzene demonstrates that knowledge of environmental fate and transport is essential for evaluating the potential permeation risk of contaminants because the distribution of chemicals among environmental media determines the contaminant levels that plastic pipes might encounter in the field. In the unsaturated soil, plastic pipe permeation was believed to occur from the vapor phase (Holsen et al, 1991b;Park et al, 1991). The current study did not collect vapor samples for BTEX analysis, and thus the exact concentration of BTEX in soil gas was unknown during the experimental period.…”
Section: Impact Of Hydrocarbons On Pe/pvc Pipes and Pipementioning
confidence: 95%
See 2 more Smart Citations
“…These volatile organic compounds (VOC) can readily diffuse through plastic pipe and migrate into water within the pipe. Holsen et al (1991) have reported permeation incidents in connection with plastic piping materials at abandoned industrial sites, near bulk chemical storage tanks and electroplating facilities, as well as at residential sites (e .g., adjacent to or near storage tanks at service stations or dry cleaning operations). If sustained, contact with these VOCs may permanently degrade the integrity of the pipes.…”
Section: Leaching and Permeationmentioning
confidence: 99%